A Medicago truncatula SWEET transporter implicated in arbuscule maintenance during arbuscular mycorrhizal symbiosis - An, Jianyong (The New phytologist, 2019)
© 2019 The Authors. New Phytologist © 2019 New Phytologist Trust.